Opportunities of Different Generations Participation in Rural Community Activities - Gintarė Vaznonienė; Ilona Kiaušienė (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
The success of rural community vitality and development is based on communication, participation and collaboration among different generations. Theoretical and empirical findings disclose that there is a lack of systematic approach characterising different generations (in this article young and elderly social groups) participation in local activities, not much attention is given to activities which join young and elderly groups whether to maintain young people in rural area or actively include elderly to common activities. Accordingly this article aims to explore participation forms and methods of different generations (youth and elderly) participation in rural community activities. The methodological background of this research is based on theoretical research methods, statistical data analysis and analysis of case of different generations’ participation in Šiauliai district municipality rural community activities. The research results disclose that different generations participation in rural community activities are various, but depends on rural areas and rural community‘s specific features. The suggested scheme based on evaluation of different generations’ participation in rural community activities can be adopted to any rural area and rural community, but being aware about the current situation of youth and elderly, also activities which are possible to be implemented in particular rural community.